Privacy and Security in Healthcare Framework: a Review (Scientific Journal for Publishing in Health Research and Technology, 2025)
The healthcare framework is one of the components to secure patient information. The significance of the healthcare domains is actually focusing on privacy and security and accessibility of users. Cloud computing and the Electronic Health Records (EHRs) and the related reduction in cost cannot be disregarded as a component in the conveyance of medicinal services advantage. Be that as it may, decreased cost is one of the targets anticipated in the utilization of EHR, which is joined by potential dangers, either when clients utilize human services or circulation of the nation's part, to protection and safety. The structure for healthcare protection is a mix of established, statutory, and administrative law at the government and state levels to guarantee security and safety everywhere throughout the world. This study has an interest in observing the main advantages and showing the disadvantages of some healthcare frameworks as described by the authors. The result of this study, which is presented throughout tables of comparisons between healthcare frameworks, can be used as a guideline for other researchers and healthcare organizations.
Keywords: Healthcare; Privacy; Healthcare standards; Security; Data Privacy